English Voice Records: ELT Students' Perceptions and Problems - Joko Prayudha.S (Didascein : Journal of English Education, 2024)
When learning a foreign language, someone must understand the target language to establish a good communication interaction. In learning English, it is very necessary to master the language to create very broad international communication. This study examined the perceptions and problems faced by students when making voice record in English to practice English speaking skill. The sample in this study consisted of 36 students who were studying English. The data were obtained through observation, questionnaires, and interviews on the perceptions and problems experienced by students when practicing speaking English using a voice recorder. Data was analyzed in three stages: reduction, display, and conclusion. The study results show that using English voice recordings can help students practice speaking English. Students also feel better and more confident practicing communicating using voice records, which provides an improvement in communicating. However, students face several problems when practicing speaking English using voice records, including inauthentic abilities, a lack of interaction, and not having good fluency if practiced directly without voice note media.